Desenvolvimento e validação de um método de quantificação de canabinoides em produtos apreendidos e matrizes medicamentosas por Cromatografia líquida de alta eficiência acoplada à Espectrometria de Massas (UHPLC-MS) - Almeida, João Victor Macedo de (2025)
Cannabis sativa L. is an ancient species cultivated for various applications, including recreational and medicinal use. Nowadays, the demand for its products has grown significantly, leading to an increase in the search for medicinal oils and a rise in smuggling, making it the main trafficked drug. In this context, our work optimized the extraction process of CBD, CBN, CBC, CBDA, Δ9-THC e Δ9-THCA in oil Cannabis and marijuana samples, varying solvent, sonication and vortex agitation time, as well as validated a determination method for seven cannabinoids using Ultra-Performance Liquid Chromatography coupled with low-resolution Mass Spectrometry (UHPLC-LTQ-MS), according to the RDC 166 of 2017 guidelines. The optimization showed that ethyl acetate was the most suitable solvent for oil extraction. For the marijuana sample, the extraction was performed with ethyl acetate as the solvent, using sonication and vortex agitation for 10 and 7.5 minutes, respectively. No matrix effect was observed in the presented method, and LOQ ranged between 1 and 5 ng. mL⁻¹, and LOD between 0.3 and 1.5 ng. mL⁻¹. Recovery ranged from 84.6 to 107.6% in oil and 80.6 to 105.9% in marijuana. Precision was evaluated in three ways: within a single day (RSD: 3.14–10.87% in oil, 3.25–10.14% in marijuana), across different days with a second analyst (RSD: 1.98–10.71% in oil, 4.65–12.81% in marijuana), and laboratories with a third analyst (RSD: 5.59–13.94% in oil, 4.65–13.56% in marijuana). The proposed method offers high sensitivity, selectivity, and precision, being adequate and satisfactory for quantifying CBD, CBN, CBC, CBDA, Δ⁹-THC, and Δ⁹-THCA